Irony as Social Criticism in Instagram Comments: A Study on “Liga Korupsi Indonesia” - Giyatmi; Arumi, Sihindun; Wijayava, Ratih (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Irony is often employed as a form of social criticism, particularly in online discourse. This study examines the function of irony in comments on the Instagram Reel Liga Korupsi Indonesia (LKI). This qualitative descriptive study aims to identify the various roles irny plays in user comments on the Instagram Reel “LKI” The qualitative descriptive method is appropriate as it allows an in-depth exploration of irony as a linguistic phenomenon within the context of social media interactions. In accordance with the problems in this study, the writers use theories related to the function of irony found from several articles discussing the function of irony from several perspectives. Data, ironic comment, were collected through documentation and content analysis, while triangulation was ensured through methodological and theoretical approaches. The writers identified six primary functions of irony in the comments: (a) a subtle form of criticism (12 out of 76), (b) intensifying condemnation or